Supplier Reliability and Inventory Management Performance in DP Manufacturing Company: Basis for Action Plan - Esparcia, Jasmin Reine A. (International Journal of Research in Interdisciplinary Studies, 2025)
This study explores the relationship between supplier reliability and inventory management performance at DP Manufacturing Company, a key player in the automotive parts sector. Using a descriptive-correlational research design, data were collected from 66 employees across various company departments using stratified random sampling in 2024. A three-part survey assessed supplier reliability, focusing on lead time, order accuracy, and defect rates, alongside inventory management performance, which was evaluated through planning and forecasting, stock level management, and inventory holding costs. The findings revealed a positive relationship between supplier reliability and inventory management performance, though the correlation was relatively weak. While supplier reliability was generally perceived as reliable, challenges were identified in defect prevention and lead time accuracy. Inventory management performed well in planning, forecasting, and cost efficiency but required improvements in stock-level management. The study found no significant impact of inventory management performance on supplier reliability. These results suggest that while enhancing supplier reliability can contribute positively to inventory management, other factors also play a critical role. The study proposes an action plan to address key areas of improvement, including enhanced forecasting, better supplier performance evaluations, and stronger supplier partnerships.